EFFECTS OF INTEGRATED FINANCIAL MANAGEMENT SYSTEM ON FINANCIAL PERFORMANCE OF COUNTY GOVERNMENTS OF KILIFI - Malala, Bonface; Kashero, Sabastian; Abuga, Isaac (International Journal For Research In Business, Management And Accounting, 2023)
The study focused on analyzing impact of the Integrated Financial Management System (IFMIS) on performance of Kilifi County government. In this perspective, the study therefore investigated the effect of timely reporting on expenditure through management system, the influence of IFMIS on effective procurement system, the effect of cash management system as well as the impact of budget planning in the County. The statement of the problem focused on need to improve resource management at Kilifi county through establishment and strengthening of IFMIS system. In this regard, auatomation of Kilifi County processes through IFMIS was key to redefine county resource management and develop new models as well as formulate regulations and policies as a strategy to mainstream IFMIS across county departments. This will result to efficient governance by providing real time financial information and enhance transparency and accountability, reducing political discretion and acting as a deterrent to corruption and fraud. The study adopted descriptive survey design followed by data collection from 121 out of 130 respondents. Collected data through questionnaires captured through a 5-point Likert scale. Descriptive statistics using means and standard deviation was analyzed. Inferential statistics was conducted through regression coefficient model to analyze the relationship selected dependent and independent variables. Analyzed data was presented in form of tables and charts. The results suggest that establishment of IFMIS had effect on timely reporting of expenditures, effective procurement, cash management as well as budgeting. The study concluded that strengthening mainstreaming of IFMIS in Kilifi County could improve financial performance by 67%. Additional research should be conducted to analyse other variables influencing County financial performance.